Sources of Confusion in Infant Audiovisual Speech Perception Research - Shaw, Kathleen E.; Bortfeld, Heather (Frontiers in Psychology, 2015)
Speech is a multimodal stimulus, with information provided in both the auditory and visual modalities. The resulting audiovisual signal provides relatively stable, tightly correlated cues that support speech perception and processing in a range of contexts. Despite the clear relationship between spoken language and the moving mouth that produces it, there remains considerable disagreement over how sensitive early language learners—infants—are to whether and how sight and sound co-occur. Here we examine sources of this disagreement, with a focus on how comparisons of data obtained using different paradigms and different stimuli may serve to exacerbate misunderstanding.